Pattern of nutrient dynamics through litterfall in Melia composita plantation with different 82espacements under agroforestry - Singh, Baljit; Kaur, Harmandeep; Gill, Rishi; Kaur, Navneet; Singh, Avtar (Indian Journal of Agroforestry, 2023)
Litterfall addition from tree species leads to return of a considerable amount of organic matter and nutrients to the soil. The study on litterfall addition and nutrient return was conducted in a Melia composita Willd. (burma dek) plantation having three spacings [5 x 3 m, 7 x 3 m (paired at 2.5 m) and 7 x 3 m] in an agroforestry system during its 4th, 5th and 6th year of age. The growth parameters of plants, quantity of litterfall addition during different months, concentration and return of nutrients (N, P and K) through litterfall and changes in soil organic carbon (OC) and available nutrients (N, P and K) were determined. The DBH (18.47 cm) and height (16.19 m) of plants after 6 years of growth were higher in 7 x 3 m spacing than the other two spacings. The total litterfall addition during 4th, 5th and 6th year was highest (4.04, 4.64 and 5.05 t/ha, respectively) in 7 x 3 m (paired at 2.5 m) spacing and lowest (2.64, 3.48 and 3.95 t/ha, respectively) in 7 x 3 m spacing. Litterfall addition was higher in December than October, November and January. The concentration of nutrients was highest in October during every year and decreased in succeeding months. The return of N, P and K averaged over age was significantly higher (39.42, 6.51 and 32.39 kg/ha, respectively) in 7 x 3 m (paired at 2.5 m) spacing than the other spacings. Soil OC, available N, P and K were higher under trees than their initial status and their content was highest (4.17 g/kg, 144.2, 19.27 and 196.3 kg/ha, respectively) in 5 x 3 m spacing. Therefore, it is concluded that the inclusion of Melia composita in the cropping systems can sustain the soil health due to addition of litterfall from the trees.